TLR-4 cooperates with Dectin-1 and mannose receptor to expand Th17 and Tc17 cells induced by Paracoccidioides brasiliensis stimulated dendritic cells - Loures, Flávio V.; Araújo, Eliseu F.; Feriotti, Claudia; Bazan, Silvia B.; Calich, Vera L. G. (Frontiers in Microbiology, 2015)
The concomitant use of diverse Pattern Recognition Receptors (PRRs) by innate immune cells can result in synergistic or inhibitory activities that profoundly influence anti-microbial immunity. Dectin-1 and the Mannose Receptor (MR) are C-type Lectin Receptors (CLRs) previously reported to cooperate with Toll Like Receptors (TLRs) signaling in the initial inflammatory response and in the induction of adaptive Th17 and Tc17 immunity mediated by CD4+ and CD8+ T cells, respectively. The protective immunity against paracoccidioidomycosis, the most prevalent fungal infection of Latin America, was previously shown to be influenced by these T cell subsets motivating us to study the contribution of TLRs, Dectin-1 and MR to the development of Th17/Tc17 immunity. First, curdlan a specific Dectin-1 agonist was used to characterize the influence of this receptor in the proliferative response and Th17/Tc17 differentiation of naïve lymphocytes induced by Paracoccidioides brasiliensis activated dendritic cells (DCs) from C57BL/6 mice. Then, WT, Dectin-1-/-, TLR-2-/- and TLR-4-/- DCs treated or untreated with anti-Dectin-1 and anti-MR antibodies were used to investigate the contribution of these receptors in lymphocyte activation and differentiation. We verified that curdlan induces an enhanced lymphocyte proliferation and development of IL-17 producing CD4+ and CD8+ T cells. In addition, treatment of WT, TLR-2-/- and TLR-4-/- DCs by anti-Dectin-1 antibodies or antigen presentation by Dectin-1-/- DCs led to decreased lymphoproliferation and impaired Th17 and Tc17 expansion. These responses were also inhibited by anti-MR treatment of DCs, but a synergistic action on Th17/Tc17 differentiation was mediated by TLR-4 and MR. Taken together, our results indicate that diverse TLRs and CLRs are involved in the induction of lymphocyte proliferation and Th17/Tc17 differentiation mediated by P. brasiliensis activated DCs, but a synergist action was restricted to Dectin-1, TLR-4 and MR.